BAWASLU COOPERATION IN COMMUNITY PARTICIPATORY SUPERVISION IN BATU CITY - Andi Setiawan (Riviera Publishing, 2025)
The General Election in Indonesia serves as a critical democratic moment where all citizens have the right to vote. However, the complexity of Indonesia’s diverse society presents challenges in ensuring a fair and transparent electoral process. The General Election Supervisory Agency (Bawaslu) plays a crucial role in participatory election supervision, involving the community in monitoring and reporting electoral violations. To strengthen public participation, Bawaslu developed various strategies, including the Participatory Supervision Program. This study aims to analyze the collaboration between Batu City Bawaslu and Islamic boarding schools (pesantren) in increasing public participation in election supervision. The research employs a qualitative descriptive method, collecting primary data through interviews with key stakeholders, including Bawaslu officials and Islamic boarding school leaders. The results indicate that cooperation between Bawaslu and pesantren is an effective approach to enhancing participatory election supervision. Through programs such as the Citizen Forum, Bawaslu successfully engaged students and religious leaders in promoting electoral integrity. Additionally, persuasive communication strategies played a significant role in bridging the gap between Bawaslu and previously uninvolved pesantren communities. In conclusion, collaboration with pesantren serves as an innovative strategy for strengthening community-based election oversight. This research highlights the importance of religious institutions in fostering democratic awareness and ensuring fair elections. Further efforts are needed to expand participatory supervision networks and enhance public engagement in the electoral process.